Paginas Desconocidas de Manuel J. Calle - Calle, Manuel (Revista Universidad de Guayaquil, 1998)
They were published in the newspaper El Grito del Pueblo Ecuatoriano in the July 1914 editions, during the days of the Civil War of Esmeraldas and Manabí, organized by Carlos Concha Torres.The material on these pages has not been published in any book. It is essential for the country’s historical studies to continue rescuing the scattered works of Manuel J. Calle, who published his Charlas under the pseudonym Ernesto Mora.